Estimating the Effects of Trade Agreements: Lessons from 60 Years of Methods and Data - Mario Larch; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2023)
Starting with Tinbergen (1962), quantifying the effects of regional trade agreements (RTAs) on international trade flows has always been among the most popular topics in the trade literature. Also not surprisingly, to estimate the effects of RTAs, most researchers and policy analysts have relied on the workhorse model of trade–the gravity equation. Over the past 60 years, there have been many important developments in the RTA literature, both in terms of better methods to quantify their effects, and also in terms of more and higher quality data. The objective of this paper is to trace the evolution of the methods and data developments in the RTA literature, from Tinbergen's very first exploration until today, and to critically evaluate their significance for our ability to measure the impact of RTAs (and other policies) on international trade.
Keywords: F10; F14; F16; 330; regional trade agreements; gravity equation; estimation; methods; data